Assessment of Ergonomic Parameters of Rice Transplanters for Women Operators - GORLA GAYATHRI; Dr. Bini Sam (Guide) (Tavanur 2017 Kelappaji College of Agricultural Engineeirng and Technology)
Assessment of Ergonomic Parameters of Rice Transplanters for Women Operators
Assessment of Ergonomic Parameters of Rice Transplanters for Women Operators